Echocardiographic assessment of tricuspid regurgitation and pericardial effusion after cardiac device implantation - Wiechecka, Katarzyna (Cardiol J, 2020)
BACKGROUND: The frequency of cardiac implantable electronic device (CIED) implantations is constantly increasing. Pericardial effusion (PE) and tricuspid regurgitation (TR) may occur after CIED implantation. The aim of the present study is to evaluate the prevalence and risk factors for new occurrences or progression of TR and PE early after CIED implantation. METHODS: This is an on-going, single-center, observational study of patients after their first CIED implantation, with an echocardiographic evaluation within 60 days before and 7 days after the procedure. Data are presented for first 110 consecutive patients who underwent CIED implantation from August 2015 to July 2016. RESULTS: Median age was 75 years, and 44% were women. In total, 87 (79%) pacemakers, 21 (19%) implantable cardioverter-defibrillators and 2 cardiac resynchronization therapy devices were implanted. After CIED implantation, there was TR progression in 17 (16%) patients: 5 patients developed moderate TR, none developed severe TR. An increase in TR was more often observed after implantations performed by operators in training than by certified operators (35% vs. 12%, p = 0.02). New PE after the procedure was observed in 8 (7%) patients and was trivial (< 5 mm) in all cases. Patients with new PE after implantation had lower baseline hemoglobin levels and tended to be women. CONCLUSIONS: New PE and an increase in TR severity are rare complications early after CIED implantation. Operator experience might be related to TR progression. Increasing the number of patients in the current on-going study will allow a more reliable assessment of the prevalence and risk factors of these complications.